2000
DOI: 10.1086/317081
|View full text |Cite
|
Sign up to set email alerts
|

The 1999 Hercules X‐1 Anomalous Low State

Abstract: A failed main-on in the 35 d cycle of Her X-1 was observed with the Rossi X-ray Timing Explorer (RXTE ) on 1999 April 26. Exceptions to the normal 35 d cycle have been seen only twice before; in 1983 and again 1993. We present timing and spectral results of this latest Anomalous Low State (ALS) along with comparisons to the main-on and normal low states. Pulsations were observed in the 3-18 keV band with a fractional RMS variation of (0.037 ± 0.003). Spectral analysis indicates that the ALS spectrum has the sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 32 publications
8
47
1
Order By: Relevance
“…Such lows happen irregularly on a time scale of ∼5 yr or ∼10 yr. It is a known feature that the flux fades gradually when going into such a low (Coburn et al 2000). We would like to point out that the perfect correlation between flux and E cyc (Fig.…”
Section: Summary Of Observational Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Such lows happen irregularly on a time scale of ∼5 yr or ∼10 yr. It is a known feature that the flux fades gradually when going into such a low (Coburn et al 2000). We would like to point out that the perfect correlation between flux and E cyc (Fig.…”
Section: Summary Of Observational Resultsmentioning
confidence: 77%
“…For better readability of the light curve, only a few error bars are shown. Three anomalous lows (Coburn et al 2000) can be recognized (indicated by AL). The rather low flux value of the latest NuSTAR observation is also marked (NuSTAR 15).…”
Section: A2 Intercalibration Between Asm and Batmentioning
confidence: 99%
“…The latest anomalous low-state is the longest ever observed, lasting 1.5 years. During the beginning of this anomalous low-state a rapid spin-down of the pulse period was observed (Parmar et al 1999;Coburn et al 2000), which was interpreted as resulting from a torque-reversal, possibly caused by a reversal of the rotation of the inner disk (see e.g., van Kerkwijk et al 1998). …”
Section: Introductionmentioning
confidence: 99%
“…(Roberts 1974;Petterson 1975;Pringle 1996;Shakura et al 1999). A reduced accretion and a reduction in the inclination of the accretion disk has been proposed to be the cause for the ALS by Coburn et al (2000). The reduced accretion leads to the decrease in the spin-up rate or even spin down in extreme circumstance, however, such a model does not account for the delay in the 35 day cycle which simply amounts to resetting the clock at an arbitrary epoch.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of pulse period obtained during the preceding normal state, indicated that the source had switched to a rapid spin-down mode compared to its normal spin-up behaviour. (Parmar et al 1999;Levine & Corbet 1999;Coburn et al 2000). Using BeppoSAX observations during the first main-on after the anomalous low state, Oosterbroek et al (2001) have reported the evidence that the rapid spin down of the source continued during the entire ALS period and the source pulse period changed to the value observed in 1984/5.…”
Section: Introductionmentioning
confidence: 99%